(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The writing of this paper is based on the need to expand the link between the teaching-learning process of the Defense Preparation discipline with the Mathematical Sciences discipline of the study plan of the Bachelor’s degree in Accounting and Finance. For this purpose, special attention is paid to the issue concerning National Security and general aspects of the discipline of Mathematical Sciences. During the development of the research, basic elements on the conceptualization of security and specifically national security were analyzed. A synopsis on vulnerability and the constant siege by the United States is also put forward for readers’ consideration. After an exhaustive bibliographic review emerges the obligation to link with greater intentionality the knowledge system of the discipline of Mathematical Sciences with the aforementioned topics. This reason supports the group of general actions proposed, as well as the definition of the part of the content related to National Security.